2016
DOI: 10.1093/ndt/gfw020
|View full text |Cite
|
Sign up to set email alerts
|

Frequent monitoring of mineral metabolism in hemodialysis patients with secondary hyperparathyroidism: associations with achievement of treatment goals and with adjustments in therapy

Abstract: Background: Dialysis guidelines in Japan recommend more frequent measurement of mineral metabolism markers than the Kidney Disease: Improving Global Outcomes guidelines. However, the extent to which frequent marker measurement contributes to achievement of target ranges and to therapy adjustment is unknown. Methods: This multicenter cohort study involved 3276 hemodialysis patients with secondary hyperparathyroidism. Data on laboratory measurements and drug prescriptions were collected every 3 months. Main expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…They found no evidence that more frequent measurements were of value when calcium, phosphorus, and PTH were already in target range. 17 Recent work by our group highlighted the stability of target achievement for anemia and CKD-MBD parameters after a de-escalation of blood sampling frequency from monthly to every 6 weeks at a single dialysis program in Ontario. 18 No change in mortality was observed after this change in practice.…”
Section: Discussionmentioning
confidence: 99%
“…They found no evidence that more frequent measurements were of value when calcium, phosphorus, and PTH were already in target range. 17 Recent work by our group highlighted the stability of target achievement for anemia and CKD-MBD parameters after a de-escalation of blood sampling frequency from monthly to every 6 weeks at a single dialysis program in Ontario. 18 No change in mortality was observed after this change in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, en aquellos pacientes con PTHi elevada y expuestos a intervenciones terapéuticas, la medición mensual (cuatro semanas) de esta hormona se relaciona con un mejor control (Fig. 2) 14 .…”
Section: Recomendacionesunclassified
“…Furthermore, routine laboratory tests for Japanese dialysis patients still remain more frequent than those recommended by the KDIGO, even after the bundling of dialysis fees. We analyzed whether such frequent tests were really beneficial and found that among those who had serum parameters above the upper limit of the ranges, more frequent tests were associated with better achievement of the target ranges [41] .…”
Section: Clinical Practice Pattern and Guideline For Ckd-mbd In Japanmentioning
confidence: 99%